(3TQM dH GdCdHGHs - (3YHO GdefYe Hf eMeO GdHQbhejfj GdCHQbhgj, TeS GdOjfs
(3ChdgG (B:s
(3CeG HYO, aEf CQLM GdeWGdH JYde GdYdhe GdESdGejI hGaJbGQgG Edi Yde GdfMh Hjf dG jOaY s
(3BNQgG (B:s
(3bGd SjHhjg(B: (3SeYfGge jbhdhf Efg bO aYd gPG BNQ eG CQOfG EjQGOg aj TQM dH GdCdHGH s
(3HgG fXGe GdJYbjHIs
(3aj GdUaMI GdChdi SWQ JGda PgH Hg GddUbs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B202 s
Keywords: (3GdfMhs